BS EN 3672. Aerospace series. Shank nut, self-locking, in heat resisting nickel base alloy NI-P101HT (Waspaloy), silver plated, for 30° swage. Classification. 1 210 MPa (at ambient temperature) / 730 °C. (27th March 2023) - British Standards Institution,
No abstract available